ROLE OF ENTREPRENEURIAL CULTURE IN ENHANCING APPRENTICESHIP PROGRAMS AND PROMOTING YOUTH-DRIVEN BUSINESS CREATION IN NIGERIA - Emmanuel Abiodun Alagbe; Rasheed Olawale Olawoyin; Ademola Samuel Sajuyigbe; Clara Obiageri Ìgwè; Olusegun Samuel Ogundare; Abiola Olubunmi Akinbobola (Sampoerna University, 2025)
Apprenticeship also contributes significantly to the creation of venture in Nigeria among the youth, as it gives them practical experiences of doing business that complement their theoretical entrepreneurship training; helps them to discover the real business operations and the strategies of handling customers and their problems. This study explores the mediating effects of entrepreneurial culture on the augmentation of apprenticeship system and creation of youth-led ventures in Nigeria. Survey questionnaire was administered to 389 respondents from the four vocational centers in Lagos. Path analysis structural equation modeling (PA-SEM) was applied for data analysis using STATA statistical software package version 15. Results show there is a significant relationship between the apprenticeship system and venture creation; gender norms perceived, celebrity endorsement and the cultural belief about expected behavior individually predict venture creation, but the variables indirectly affect venture creation in partial mediation of their relation to apprenticeship training.